MARKETING STRATEGY ANALYSIS OF OVO DIGITAL WALLET CUSTOMERS INTEREST - Mutia Sari Dewi; Nuri Aslami (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
Abstract This study aims to analyze the marketing strategy of customer interest on OVO as digital wallet. This study a qualitative study in the sense that it is a library study with books and other literature serving as the primary object. The data presented is in the form of words, which requires concise and systematic processing. Analysis is a series of straightforward efforts to generate and process research material into a simple framework. The collected data is subsequently examined to obtain information, however first the data is picked for its reliability. In this study, data analysis techniques such as content analysis were used. The finding reveals that the OVO strategy for improving customer advantages through the use of online payment systems is to place emphasis on the payment transaction itself. The points that have been acquired can be redeemed at a later date if the price of the payment specification decreases. Customers can pay while still on the spot, which is surely highly efficient, practical, and quick, making it a method that streamlines the customer's experience overall. By providing a positive environment that caters to their needs, especially for the millennial generation, who happens to be the largest user of the OVO digital wallet, it will encourage them to flock to the merchants that they prefer to visit.